2013
DOI: 10.1007/jhep02(2013)149
|View full text |Cite
|
Sign up to set email alerts
|

Up asymmetries from exhilarated composite flavor structures

Abstract: We present a class of warped extra dimension (composite Higgs) models which conjointly accommodates the tt forward-backward asymmetry observed at the Tevatron and the direct CP asymmetry in singly Cabibbo suppressed D decays first reported by the LHCb collaboration. We argue that both asymmetries, if arising dominantly from new physics beyond the Standard Model, hint for a flavor paradigm within partial compositeness models in which the right-handed quarks of the first two generations are not elementary fields… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 181 publications
(306 reference statements)
0
35
0
Order By: Relevance
“…The ATLAS Collaboration, in fact, recently presented new experimental techniques designed to tag charm jets at the LHC [6]. The possibility to apply charm tagging, beyond its plain interest from the SM perspective [7,8], also opens new possibilities to analyze various beyond the SM signals [9][10][11][12]. In particular we show in this paper how crucial charm tagging may be in order to exhume the associated Higgs production signal in the case of a suppressed h → bb branching ratio due to an enhanced Higgs-to-charm coupling relative to the SM.…”
Section: Introductionmentioning
confidence: 99%
“…The ATLAS Collaboration, in fact, recently presented new experimental techniques designed to tag charm jets at the LHC [6]. The possibility to apply charm tagging, beyond its plain interest from the SM perspective [7,8], also opens new possibilities to analyze various beyond the SM signals [9][10][11][12]. In particular we show in this paper how crucial charm tagging may be in order to exhume the associated Higgs production signal in the case of a suppressed h → bb branching ratio due to an enhanced Higgs-to-charm coupling relative to the SM.…”
Section: Introductionmentioning
confidence: 99%
“…Sizable dijet contributions arise in the presence of a light color octet vector resonance in the effective theory [31,32,35,37]. Even if such a state is absent, as assumed here, new physics dijet sources are generically induced by unknown physics at the cut-off scale Λ ∼ 4πf .…”
Section: Indirect Constraints From Dijet Productionmentioning
confidence: 78%
“…This possibility leads to a series of interesting experimental consequences which have been partially discussed in ref. [31,32,[34][35][36][37]. We focus here on analysing signals which could be already probed by direct searches at the LHC.…”
Section: Jhep02(2014)055mentioning
confidence: 99%
See 1 more Smart Citation
“…[17] have proposed a symmetry to supress the main contributions to ǫ K in anarchic partial compositeness, however ref. [18] has shown that the suppression is spoiled once quark masses are taken into account. Ref.…”
Section: Jhep10(2017)120mentioning
confidence: 99%